Assessment of Poland's Economic Policy During te Crisis - Krajewski, Stefan (Olsztyn Economic Journal, 2013)
The rapid weakening of economic activity, covering most states in the world, gives rise to a lively discussion on the choice of methods to tackle the crisis, the legitimacy and effectiveness of various economic policies, the role of the state and the scope of its intervention in the economy. The paper evaluates the Polish economic policy in recent years. This refers to the situation prevailing in the EU and the USA. I conclude that the Polish economy during the crisis remained relatively stable, without having to provide the emergency aid from the outside. The development of such a situation has been affected by different reasons, including: - The benefits of the so-called "backwardness rent", which resulted, among others, in the inflow of EU funds (Poland was in 2007-2013 and in will be in 2014-2020 the biggest beneficiary of the EU budget); - The effects of decisions on changes in the tax and social security, taken for political reasons (before the crisis); - The controversial withdrawal from the funded pension system, reducing the budget deficit and public debt; - The prudent monetary policy and anti-inflation policy pursued over many years. Actions taken in Poland are primarily focused on reducing costs, which differs quite significantly from the economic policy dominant in the U.S. and the "old" EU countries which generally pursue expansionary fiscal policy and a policy of cheap money. Polish solution facilitates the achievement of short-term fiscal sustainability, but does not create favorable conditions for the development in the long-term (insufficient investment, petrification of economic structure, lack of innovation).